2020
DOI: 10.1093/cercor/bhaa243
|View full text |Cite
|
Sign up to set email alerts
|

Greater BOLD Variability is Associated With Poorer Cognitive Function in an Adult Lifespan Sample

Abstract: Moment-to-moment fluctuations in brain signal assessed by functional magnetic resonance imaging blood oxygenation level dependent (BOLD) variability is increasingly thought to represent important “signal” rather than measurement-related “noise.” Efforts to characterize BOLD variability in healthy aging have yielded mixed outcomes, demonstrating both age-related increases and decreases in BOLD variability and both detrimental and beneficial associations. Utilizing BOLD mean-squared-successive-differences (MSSD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…These studies have generally reported that BOLD variability is negatively related to age (lower in healthy controls) 15,16 and positively related to task performance. 12,18 However, a careful look reveals that these patterns of change in BOLD variability differ between brain regions and task requirements. For example, healthy controls presented greater BOLD variability in superior frontal and inferior temporal gyri 15 and lower BOLD variability in supplementary motor areas and inferior frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have generally reported that BOLD variability is negatively related to age (lower in healthy controls) 15,16 and positively related to task performance. 12,18 However, a careful look reveals that these patterns of change in BOLD variability differ between brain regions and task requirements. For example, healthy controls presented greater BOLD variability in superior frontal and inferior temporal gyri 15 and lower BOLD variability in supplementary motor areas and inferior frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Higher IIVRT has in general been recognized as a marker of poorer brain health (61) and to predict all-cause mortality in adults (62). Further, moment-to-moment fluctuations of brain signaling also has been suggested as an important parameter of brain health (36, 52). This not only emphasizes the general importance of better understanding the neural mechanisms that give rise to IIVRT, it underscores the need to characterize how dysfunction in this neurobiology yields the typically high IIVRT found in most patients with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…We hoped to extend prior findings of IIVRT-related neurobiology primarily learned from attention paradigms by examining a moderate-sized adolescent non-ADHD and ADHD sample who performed a Go/NoGo fMRI task (35). We predicted that Go/NoGo task hemodynamic response amplitude variability in both anterior and posterior DMN hub regions would predict higher ADHD IIVRT (24, 36, 37). Secondary expectations included that mean amplitude would predict similarly as previous Go/NoGo fMRI studies higher IIVRT in pre-motor systems (31, 38) and temporal lobe cortex (2, 23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, age differences in BOLD SD might be explained by changes in cardiovascular and cerebrovascular factors that affect the link between neuronal activity and changes in blood flow (Tsvetanov et al, 2020). Moreover, BOLD MSSD, a measure of how much the BOLD signal changes across successive observations, is more often increased rather than decreased in older adults (Boylan et al, 2021;Nomi et al, 2017;Samanez-Larkin et al, 2010), highlighting the fact that agerelated changes in signal dynamics can result in more or less "signal variability" depending on the used metric. In fact, the relationship between the non-invasive measures of brain signal variability used in human neuroscience and neuronal noise is not trivial.…”
Section: Introductionmentioning
confidence: 99%